2010
DOI: 10.1590/s1806-37132010000500017
|View full text |Cite
|
Sign up to set email alerts
|

Drogas antituberculose: interações medicamentosas, efeitos adversos e utilização em situações especiais - parte 2: fármacos de segunda linha

Abstract: Os objetivos principais do tratamento da tuberculose são curar o paciente e minimizar a possibilidade de transmissão do bacilo para indivíduos saudáveis. Reações adversas ou interações das drogas antituberculose entre si e com outros fármacos podem causar modificação ou descontinuação da terapêutica. Descrevemos os mecanismos gerais de ação, absorção, metabolização e excreção dos medicamentos utilizados no tratamento da tuberculose multidroga resistente (aminoglicosídeos, fluoroquinolonas, cicloserina/terizido… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0
10

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(34 citation statements)
references
References 39 publications
0
24
0
10
Order By: Relevance
“…In contrast, the absorption of ETH from the GI tract of the guinea pig appears to be slightly delayed (Tmax = 0.39 h), limited and variable. Despite limited reports of rapid and complete ETH absorption when administered to humans 36 , a larger number of studies describe the pattern of ETH absorption as “erratic” and that delayed absorption is typically common 23, 25, 37 . The Tmax in healthy volunteers is reported to be between 1.02 h and 2.6 h depending on the formulation (film or enteric coated tablet) and co-administration of food or antacids 23, 3840 .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the absorption of ETH from the GI tract of the guinea pig appears to be slightly delayed (Tmax = 0.39 h), limited and variable. Despite limited reports of rapid and complete ETH absorption when administered to humans 36 , a larger number of studies describe the pattern of ETH absorption as “erratic” and that delayed absorption is typically common 23, 25, 37 . The Tmax in healthy volunteers is reported to be between 1.02 h and 2.6 h depending on the formulation (film or enteric coated tablet) and co-administration of food or antacids 23, 3840 .…”
Section: Discussionmentioning
confidence: 99%
“…Others studies have found high prevalences (more than 50%) of adverse drug reactions among MDR-TB patients [26], [27] compared to the expected prevalence of mild reactions in those using first-line therapy (around 5–20%) [19]. In general, drugs for treating MDR-TB strains have greater toxicity effects and involve a long-term exposure (18 to 24 months), all in great contrast with the treatment of a sensitive strain of TB [28].…”
Section: Discussionmentioning
confidence: 99%
“…Reports have shown that there is alteration in thyroid hormone levels in patients with non-thyroid illnesses such as TB. This alteration has been attributed to anti-TB drugs especially, the secondline anti-TB drugs which cause more adverse effects than the first-line anti-TB drugs used for the treatment of drug-sensitive TB 9 . The exact mechanism responsible for the alteration is still unknown 8,10 , though the following mechanisms were suggested; viz: decreased T4 to T3 conversion, decreased TSH production and action of drugs such as ethionamide and prothionamide used for the treatment of MDR-TB on the thyroid causing hypothyroidism by inhibiting thyroid hormone synthesis through inhibition of iodine organification [11][12][13] .…”
Section: Management Of Mdr-tb Is Daunting Especially Whenmentioning
confidence: 99%